CROSS-FUNCTIONAL INFLUENCE OF BEHAVIORAL THEORIES ON THE FORMATION OF BUSINESS COMMUNICATIONS STRATEGIES (Development Service Industry Management, 2025)
The aim of the article is to explore trends in changing behavioral patterns in the context of digitalization, assess their impact on the evolution of behavioral theories, and analyze the transformation of business communication models and strategies. The authors have substantiated the hypothesis that cyber-hating emerges as part of culture and behavioral patterns due to generational theory shifts.As a result of a sociological study, the causes and motives behind cyber-hating were examined and proven, using a teenage audience as an example. A cross-functional approach was applied to identify the motives behind cyber-hating, considering the interaction between the evolution of behavioral theories in marketing, cognitive psychology, social influence psychology, and generational theory development.In the study, sociological research methods were employed, particularly surveys conducted through questionnaires. In analyzing sociological and marketing data, the following methods were applied: Rosenberg Self-Esteem Scale (RSES); Likert Scale; Scales for measuring the frequency and intensity of social media usageThe scientific novelty of the research findings lies in substantiating and proving the cross-functional interaction in the emergence of cyber-hating motives. The study identifies a new motivation factor for cyber-hating – the formation of behavioral patterns in cyberspace as a result of evolving behavioral responses in the context of generational change.This necessitates the development of business communication models and strategies that align with the expectations of different generational groups and reflect their unique behavioral patterns. The article proposes business communication strategies tailored to representatives of each generational group.The practical significance of the research findings lies in identifying specific behavioral motives of the new generation and formulating business communication strategies for each generational group. The study's practical results demonstrate the transformation of generational shifts, behavioral patterns, cultural perspectives, and values as a result of the interaction of factors in a cross-functional framework.This highlights the necessity of considering each generation's behavioral models when developing business communication strategies.
Keywords: business communication strategies; cyber-hating; generational theory; behavioral theories; sociological research; cross-functional approach